Convergent evolution in the mechanisms of ACBD3 recruitment to picornavirus replication sites - Horova, Vladimira; Lyoo, Heyrhyoung; Różycki, Bartosz; Chalupska, Dominika; Smola, Miroslav; Humpolickova, Jana; Strating, Jeroen R P M; van Kuppeveld, Frank J M; Boura, Evzen; Klima, Martin (PLoS pathogens, 2019)
Enteroviruses, members of the family of picornaviruses, are the most common viral infectious agents in humans causing a broad spectrum of diseases ranging from mild respiratory illnesses to life-threatening infections. To efficiently replicate within the host cell, enteroviruses hijack several host factors, such as ACBD3. ACBD3 facilitates replication of various enterovirus species, however, structural determinants of ACBD3 recruitment to the viral replication sites are poorly understood. Here, we present a structural characterization of the interaction between ACBD3 and the non-structural 3A proteins of four representative enteroviruses (poliovirus, enterovirus A71, enterovirus D68, and rhinovirus B14). In addition, we describe the details of the 3A-3A interaction causing the assembly of the ACBD3-3A heterotetramers and the interaction between the ACBD3-3A complex and the lipid bilayer. Using structure-guided identification of the point mutations disrupting these interactions, we demonstrate their roles in the intracellular localization of these proteins, recruitment of downstream effectors of ACBD3, and facilitation of enterovirus replication. These structures uncovered a striking convergence in the mechanisms of how enteroviruses and kobuviruses, members of a distinct group of picornaviruses that also rely on ACBD3, recruit ACBD3 and its downstream effectors to the sites of viral replication.
Keywords: Models, Molecular; Membrane Proteins; krystalizace; Humans; Picornaviridae; Host-Pathogen Interactions; Sequence Homology; konformace proteinů; Viral Proteins; Protein Binding; interakce hostitele a patogenu; Crystallization; sekvence aminokyselin; mutace; Protein Conformation; adaptorové proteiny signální transdukční; krystalografie rentgenová; Crystallography, X-Ray; lidé; HEK293 Cells; Adaptor Proteins, Signal Transducing; molekulární modely; Virus Replication; fosfotransferasy s alkoholovou skupinou jako akceptorem; Amino Acid Sequence; virové proteiny; HEK293 buňky; vazba proteinů; replikace viru; membránové proteiny; Phosphotransferases (Alcohol Group Acceptor); Mutation; sekvenční homologie